ANALISIS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN PADA PT RUKUN MITRA BERSAMA DI KABUPATEN BONE - Musdaliana; Anwar, Azwar; Ryketeng, Masdar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the internal control system in broiler inventory management at PT Rukun Mitra Bersama in Bone Regency. This study uses a qualitative descriptive approach to obtain an in-depth overview of the company's internal control system implementation in managing broiler inventory as a biological asset. The research variable used is the internal control system based on the COSO (2013) framework, which consists of five components: control environment, risk assessment, control activities, information and communication, and monitoring. Data collection techniques were carried out through observation, interviews, and documentation. Observations were conducted to directly observe the broiler inventory management process in the field, interviews were conducted with parties involved in inventory management, while documentation was used to obtain supporting data in the form of company reports and archives. The data analysis technique in this study was carried out through three stages: data collection, data reduction, and data presentation. The results of the study indicate that PT Rukun Mitra Bersama has implemented an internal control system in accordance with the COSO (2013) components, specifically in the aspects of the control environment, control activities, and information and communication. This implementation is supported by a clear division of tasks, the use of official documents, daily recording, and routine reporting by farmers and Technical Support. However, the risk assessment and monitoring components have not been running optimally because the control process is still reactive and is not supported by structured and formal written documentation and evaluation.